Weed management and herbicide selectivity in ornamental plants - Martins, D. [UNESP] (2019)
Floriculture and landscaping sector has the same problems as other crops regarding weed management. Weeds affect the yield and quality of the harvested product, in which the visual aspect and aesthetics stand out as the most important factors in flower production and landscaping. Weed control in floriculture and landscaping is critical and costly because maintaining the beauty of the product and the use of herbicides is a low-cost management tool compared to manual management. However, it implies knowing herbicide selectivity, as ornamental species may present some injury depending on the active ingredient and the degree of selectivity of the compound. Because the use of this practice in flower production and landscaping both abroad and mainly in Brazil is incipient, aspects of selectivity, chemical weed control, and safe application of different herbicides are addressed in this paper.